Peer-moderated asynchronous online discussions: a case study of peer e-moderation supports - Ghadirian, Hajar; Mohd Ayub, Ahmad Fauzi; Abu Bakar, Kamariah; Silong, Abu Daud (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Efforts to attract students’ participation in asynchronous online discussions (AOD) have taken a number of various paths; mostly on the role of instructor as moderators. Despite economical advantages proposed by peer moderation of AODs, students’ e-moderation supports have not been widely explored in Asian cultures. To better understand and address this gap, this study reports a qualitative case study exploring the peer moderators’ e-moderation supports used to attract their group mates to participate more in AODs. Data were collected from students’ discussion transcripts and log files. AODs’ density was chosen as the criterion to look for successful AODs. We deemed a peer moderator to have successfully attracted other students to participant if the AOD had a density score above the mean density score. E-moderation supports enacted by the peer moderators were then examined. Using quantitative content analysis, all e-moderation supports were identified to be adapted by peer moderators. However, knowledge construction, information exchange, and socialization supports were found to be of continuous importance.